COMPUTATIONAL STUDY: THE EFFECT OF BASIS SET ON THE ENERGY STABILITY OF HYDROCARBONS AND HALOGENIC ACIDS - Nilawati; Priadana, Yogi Surya; Priadana, Yoga Surya; Azani, Zainina; Solin, Mardia; Hamidah; Pratiwi, Ika Bella (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2024)
This research is motivated by the many base sets contained in computational calculations. The selection and use of base sets play an important role in determining the accuracy of the calculation of theoretical molecular properties as well as in lowering the BSSE (base set superposition error). This study aims to analyze the influence of base set variations on the calculation of hydrocarbon and halogen acid energy stability using computational methods. The research method used is an experimental method. Molecular modeling using Avogadro software with the molecules used are halogen acid molecules and alkanes C1 - C5. The calculation uses NwChem software with the DFT method, functional BL3YP with 4 different base sets, namely STO-3G, 321-G, cc-pVDZ, and cc-pVTZ. The resulting data is then analyzed and compared with database calculations. The results of the study show that the higher the base set used, the more accurate the calculation results obtained. The base set that shows the most accurate results in this study is cc-pVTZ. However, it should be noted that the most accurate set bases can be different for each molecule.